The Personalized System of E-Modul Instructions in Physical Education Online Learning - Agung Widodo; Djoko Pekik Irianto; Ali Satya Graha; Yudanto Yudanto; Deni Hardianto; Panggung Sutapa; Manil Karakauki; Syed Kamaruzaman Syed Ali; Agus Kristiyanto; Kukuh Wahyudin Pratama (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
The Covid-19 pandemic has disrupted the world of education which has made schools implement online learning. This situation is very challenging for Physical Education (PE) course. The study purpose was to examine the condition of physical education online learning and the needs of teachers for electronic modules based on personalized system of learning instruction models in PE online learning. Materials and methods This study used Research and Development (R&D) method with qualitative and quantitative setting using questionnaire as an instrument. 61 of 86 respondents responded and filled out the questionnaire completely between 7-14 October 2021. Results Three main findings were highlighted in this study. Firstly, the condition of PE online learning has not been effective during the Covid-19 pandemic. Teachers experienced several obstacles in implementing PE online learning. Secondly, teachers need e-modules as material for student learning independently at home. Lastly, it is necessary to apply a personalized system of instruction learning model in PE online learning. This model is believed to be appropriate and effective as an independent learning model. Conclusions PE online learning has not been effective so far. An electronic module based on a personalized system of instruction is needed to support the implementation of PE online learning.